Une pédagogie de l’engagement face à la désorientation - Jean-Yves Robin; Nathanaël Wallenhorst (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This article has the ambition to describe an academic experience now committed for twenty years. It was implemented because of the challenge of disorientation met by many students. This pedagogical scenario gets to work an educational posture : a commitment posture. In this device, the teacher as the students are invited to invest new places. These movements reveal the anthropological, philosophical and pedagogical issues ; they are explained in this contribution.